Deep-sea corals from Mar del Plata submarine canyon (Southwestern Atlantic Ocean off Argentina) - Lauretta, Daniel Marcelo (2019)
Deep-sea coral exploration has been scarce in Argentinean waters, especially in the northern region. Few expeditions have been made to the area, where the HMS Challenger (1873-1876) and the Walther Herwig (1960’s and 1970’s) expeditions took samples near Mar del Plata submarine canyon (up to 1200 m). During 2012 and 2013 three biological expeditions were made to Mar del Plata submarine canyon, and 64 sampling stations were made, from 200 to 3500 m depth. Here we present the results of the diversity of stony corals (Scleractinia), black corals (Antipatharia), zoantharians (Zoantharia), stylasterids (Hydrozoa: Stylasteridae), sea pens (Pennatulacea) and primnoids (Alcyonacea: Primnoidae) found. Corals were present in most of the stations, from 201 m to 3282 m depth. Stony corals were more abundant in number of specimens, with at least 10 species, most within Flabellum, Javania and Fungiacyathus. Primnoids were the more abundant group in number of species (at least 20), distributed mostly within Convexella, Heptaprimnoa, Onogorgia, Plumarella, Primnoella and Thouarella. Stylasterids and sea pens presented about the same number of species (14 and 13 respectively) within Cheiloporidion, Conopora, Crypthelia, Errina, Errinopora, Errinopsis, Inferiolabiata, Lepidopora, Sporadopora, Stellapora and Stylaster for stylasterids, and Anthoptilum, Kophobelemnon, Distichoptilum, Umbellula, Protoptilum, Malacobelemnon, Amphiacme and Funiculina for sea pens. Few specimens of zoantharians were found, all within Epizoanthus. Finally, 11 specimens of Dendrobathypathes grandis (Antipatharia) were found, the only black coral reported for the southern region of the southwestern Atlantic Ocean off Argentina. Two new species were described, and several more are been described. Despite the low quantity of works dealing with deep-sea corals in Argentina so far, the group is abundant and diverse. Corals are most likely to be present all along the Argentinean sea (specially beyond 200 m depth).